Wear Characteristics of Ceramic Tools When Turning BN Free-Machining Steel - Ryutaro TANAKA; Akira HOSOKAWA; Tatsuaki FURUMOTO; Takashi UEDA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2013)
This study examined the wear characteristics of ceramic tools when turning BN free-machining steel based on AISI 1045. An experiment was conducted to investigate why the alumina TiC-based ceramic tool showed remarkably better cutting performance than a pure alumina ceramic tool. The tool flank temperature, cutting force, and element distribution on the wear part were investigated. The cutting force and tool flank temperature of the BN free-machining steel were lower than those of standard steel, and the alumina TiC-based ceramic tool allowed for a lower cutting force and tool flank temperature than the pure alumina ceramic tool. After cutting of the BN free-machining steel, on the rake face, a deposited layer containing Al and N was detected, and the amount of the deposited layer on the alumina TiC-based ceramic tool was more than that on the pure alumina ceramic tool. Therefore, using an alumina TiC-based ceramic tool suppresses the tool flank temperature and makes it easier for a protective nitride layer to stick on the wear part; as a result, it has a clearly superior tool wear resistance than an alumina ceramic tool.